Application of the DAREA/DAPSA score for assessment of disease activity in psoriatic arthritis. Issue 8 (4th June 2010) - Schoels, Monika; Aletaha, Daniel; Funovits, Julia; Kavanaugh, Arthur; Baker, Daniel; Smolen, Josef S
Abstract : Background and objectives: Instruments for measuring disease activity in psoriatic arthritis (PsA) are not yet firmly established, and most of the currently employed ones have been derived for rheumatoid arthritis. Some of these instruments are based on 28 joint counts, which do not capture joints frequently affected in PsA. Therefore, the reliability and validity of DAREA (for 'Disease Activity index for REactive Arthritis'), which was originally developed for reactive arthritis and employs a 66/68 joint count, was tested in patients with PsA. Methods: Trial data from the Infliximab Multinational Psoriatic Arthritis Controlled Trial were analysed. Results were then independently validated using an observational data set. DAREA was compared to other composite indices regarding correlations with core set variables, sensitivity to change and criterion validity. Results: Good correlation of the DAREA with single items of disease activity, other composite scores (r=0.6−0.9) and physical function (Health Assessment Questionnaire; r=0.5) was found. Likewise, DAREA was at least as sensitive to change as the other indices and more so in patients with distal interphalangeal joint involvement. Additionally, DAREA correlated well with radiographic changes. Conclusion: The analyses of this study provide evidence of the utility and validity of the DAREA for PsA disease activity assessment. A second name should therefore be assigned to this score: DAPSA (for 'Disease Activity index for PSoriatic Arthritis').